2015
DOI: 10.5812/asjsm.24050
|View full text |Cite
|
Sign up to set email alerts
|

Training Effects on Immune Function in Judoists

Abstract: Background:It has been reported that high intensity long term training in elite athletes may increase risk of immune function.Objectives:This study is to examine training effects on immunoglobulin and changes of physiological stress and physical fitness level induced by increased cold stress during 12-week winter off-season training in elite Judoists.Patients and Methods:Twenty-nine male participants (20 ± 1 years) were assigned to only Judo training (CG, n = 9), resistance training combined with Judo training… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
14
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 26 publications
2
14
1
3
Order By: Relevance
“…11 The intensity and the amount of training during NF-OR may be responsible for changes in the immune function, such as the change in the phagocytic activity of defense cells, reduced production of immunoglobulin A and increased oxidative stress. 29 The NF-OR state can lead to OTS which presents more diffuse characteristics, negatively affecting multiple systems and having a much slower recovery process.…”
Section: Non-functional Overreachingmentioning
confidence: 99%
“…11 The intensity and the amount of training during NF-OR may be responsible for changes in the immune function, such as the change in the phagocytic activity of defense cells, reduced production of immunoglobulin A and increased oxidative stress. 29 The NF-OR state can lead to OTS which presents more diffuse characteristics, negatively affecting multiple systems and having a much slower recovery process.…”
Section: Non-functional Overreachingmentioning
confidence: 99%
“…Owen et al (2016) showed that high intensity soccer training might cause a significant decrease in s-IgA values post-exercise as compared to low intensity training (2). Lee et al (2015) indicated that there was reduced trend of IgA in male adults after 12 weeks of Judo training or resistance combined with Judo training or interval training combined with Judo training (3). sptusnueytotuytmehue mlplpooulo u One of these heavy trainings is High-intensity Interval Training (HIIT) being performed by athletes in order to improve their exercise performance.…”
Section: Introductionmentioning
confidence: 99%
“…A avaliação da potência aeróbia máxima pode trazer informações relevantes aos técnicos/treinadores, possibilitando a comparação do estado de condicionamento aeróbio dos atletas (BAUDRY; ROUX, 2009;FRANCHINI et al, 2011), utilizar dos parâmetros para a prescrição das intensidades do treinamento contínuo (ALMANSBA et al, 2010;BONATO et al, 2015) e intermitente de alta intensidade (KIM et al, 2011;BONATO et al, 2015;LEE et al, 2015), além de ser utilizado para monitorar os efeitos de um programa de treinamento (ALMANSBA et al, 2010;KIM et al, 2011;BOROWIAK et al, 2012;LEE et al, 2015;FRANCHINI et al, 2016a;FRANCHINI et al, 2016b). A potência aeróbia máxima pode ser mensurada por meio de um teste progressivo até a exaustão, os quais são comumente realizados em ambientes laboratoriais: esteira ou ciclo-ergômetros de membros inferiores e superiores (BAUDRY; ROUX, 2009;FRANCHINI et al, 2011;FRANCHINI et al, 2016a;JULIO et al, 2017a), no entanto, esse tipo de teste apresenta baixa validade ecológica na avaliação das adaptações específicas, assim como na utilização dos resultados para a prescrição do treinamento específico da modalidade (DAVIDS, 1988;FRANCHINI et al, 2016a;CHAABENE et al, 2018a).…”
Section: Introductionunclassified
“…, a aptidão aeróbia baseia-se em dois componentes principais: capacidade aeróbia e potência aeróbia máxima. A capacidade aeróbia está relacionada à maior intensidade de esforço mantida por períodos prolongado de tempo (MATSUHIGUE; LIMA; KISS, 2003; FRANCHINI; Portanto, os autores concluíram que a maior potência aeróbia máxima pode auxiliar no desempenho de exercícios intermitentes anaeróbios.Com relação ao treinamento, é muito comum os atletas estarem engajados em rotinas de treinamento aeróbio para melhorarem o desempenho dessa capacidade física(KIM et al, 2011; BOROWIAK et al, 2012;TAKITO et al, 2014;LEE et al, 2015) KIM et al (2011). demonstraram que oito semanas de treinamento…”
unclassified
See 1 more Smart Citation